The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1063/1.438564
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy of molecular constituents of one-dimensional organic conductors. Tetrathiofulvalene (TTF), TTF+, and (TTF+)2 dimer

Abstract: An extensive vibrational assignment of TTF and TTF-d4 is achieved, improving the previously reported one through the use of polarized infrared spectra of single crystals of the monoclinic form. Infrared spectra of the monoclinic and triclinic forms are compared and the different crystal field effects discussed. Powder Raman and infrared spectra of (TTF)Br1.0 and (TTF-d4)Br1.0, Raman depolarization ratios and infrared spectra of (TTF)ClO4 and (TTF-d4)ClO4 solutions are reported. The assignment of the ag, b1u, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(141 citation statements)
references
References 58 publications
14
125
0
2
Order By: Relevance
“…Yet, the structure of TTF is planar in the condensed phase and allows us to imply D 2h . The labeling of the modes in Table 2 is according to Girlando et al [49] and Bozio et al [47]. The calculations reveal an inner distance of the C=C double bonds in TTF 0 of 1.346 Å, which agrees very well with the experimentally determined value of d = 1.35 Å in the gaseous phase [46].…”
Section: Ab-initio Calculations: Band Structure Optical Spectra and supporting
confidence: 78%
See 2 more Smart Citations
“…Yet, the structure of TTF is planar in the condensed phase and allows us to imply D 2h . The labeling of the modes in Table 2 is according to Girlando et al [49] and Bozio et al [47]. The calculations reveal an inner distance of the C=C double bonds in TTF 0 of 1.346 Å, which agrees very well with the experimentally determined value of d = 1.35 Å in the gaseous phase [46].…”
Section: Ab-initio Calculations: Band Structure Optical Spectra and supporting
confidence: 78%
“…The intensity also increases slightly, as predicted by the theoretical calculations (see Table C2 in Appendix C). At room temperature, further weak maxima can be recognized at higher frequencies, which we ascribe to the ν 25 (b 2u )-mode of TTF [47]. According to Table C2, theory predicts the mode to appear at ν = 802 cm −1 , but it is shifted due to the ionicity, in this case to 805 cm −1 .…”
Section: B-directionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assignments used were the solution values of Bozio et al 11 and with the exception of the assignment of 530 cm Ϫ1 as a B 2g mode these were also the assignments used by Liu et al 12 We favor an assignment of the B 2g mode at 250 cm Ϫ1 based on the bands observed in this region in both the INS and Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Eldridge et al 9 have studied the room temperature infrared and Raman spectra of BEDT-TTF and four of its isotopic analogs and report a modified valence force model that successfully predicts most of the in-plane and a few of the ethylene out-of-plane modes. The work of Bozio et al 10,11 remains the definitive infrared and Raman study of TTF and TTF 1.0 and their force fields satisfactorily explain most of the in-plane modes. More recently, Liu et al 12 have used a combination of density functional theory and ab initio MP2 calculations to study the structures and vibrational spectra of both BEDT-TTF and TTF.…”
Section: Introductionmentioning
confidence: 99%